The Influence of Fanaticism and Consumptive Behavior Towards Financial Literacy in K-Pop Fans: A Study In An Entrepreneurship-Based University - Chandra, Evelyn Venoria (Universitas Ciputra Surabaya, 2022)
This study aim to examine the effect of fanaticism and consumptive behaviour on financial literacy among K-pop fans. This study uses a quantitative approach with multiple linear regression and sample of 243 respondents from population of 563 people was collected through questionnaires. The result of this study is fanaticism affects financial literacy in a significant positive way, but consumptive behaviour does not affect financial literacy in K-pop fans, which is an interesting finding from this study because the research sample is student who study at entrepreneurship-based-universities.